Policy Transformations about ICT Applying in Learning and Teaching in Vietnamese General Educational System - Thi Thanh Hai, Pham; Nguyen, Nguyen Duc (VNU Journal of Science: Education Research, 2020)
Informatiom Communication Technology (ICT) has an important place in the educational innovation program. New policies on educational innovation are built on the premises and prospects of effective ICT application in teaching and learning (Richards, 2004). Studies on ICT application in teaching and Electronic Book or Digital Hydbrid Text in Education and Training have been researched and developed by serveral countries in the US and Europe. This article analyzes some policies for ICT application in teaching and educational innovation in Vietnam. These policies are analyzed according to the approaches to the Government of Vietnam Orientation on the application of information technology in education; The Ministry of Education and Training's policies on the Vietnamese education renovation requirements, ICT equipment infrastructure, the capacity of teachers to apply ICT in teaching. The research results show that the government has tried to give directions for ICT to be widely applied from management to teaching activities. The Ministry of Education and Training has also issued circulars and specific instructions to promptly implement orientations from the government. However, the approach to applying ICT in education has many multidimensional and too broad theoretical bases. The instructions on ICT are too sketchy and not yet specific for the application of ICT in teaching and learning.